2023
DOI: 10.1161/circep.122.011780
|View full text |Cite
|
Sign up to set email alerts
|

Paroxysmal Atrial Fibrillation Ablation Using a Novel Variable-Loop Biphasic Pulsed Field Ablation Catheter Integrated With a 3-Dimensional Mapping System: 1-Year Outcomes of the Multicenter inspIRE Study

Abstract: Background - The inspIRE study evaluated safety and effectiveness of a fully integrated biphasic pulsed field ablation (PFA) system with a variable loop circular catheter for the treatment of drug-refractory paroxysmal atrial fibrillation (AF). Methods - Subjects underwent pulmonary vein isolation (PVI) with the PFA system, using at least 12 applications per vein; adenosine/isoproterenol was administered to confirm entrance block. Wave I assessed initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 21 publications
5
71
0
Order By: Relevance
“…In the MANIFEST-PF registry, the rate of major procedure-associated adverse events was low and consistent with other contemporary AF ablation studies using PFA and did not differ significantly between the sex groups (female: 2.5% vs male: 1.5%). Major adverse events mostly consisted of cardiac tamponade (female: 1.4% vs male: 1.0%; P = .46) and stroke (0.4% vs 0.4%, P >.99).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In the MANIFEST-PF registry, the rate of major procedure-associated adverse events was low and consistent with other contemporary AF ablation studies using PFA and did not differ significantly between the sex groups (female: 2.5% vs male: 1.5%). Major adverse events mostly consisted of cardiac tamponade (female: 1.4% vs male: 1.0%; P = .46) and stroke (0.4% vs 0.4%, P >.99).…”
Section: Discussionsupporting
confidence: 89%
“…The primary effectiveness outcome of freedom from atrial arrhythmia recurrence (>30 seconds after blanking) was 79.0% in male patients and 76.3% in female patients at 12 months of follow-up, with greater overall effectiveness in the paroxysmal AF cohort (male: 82.5% vs female: 80.2%; P = .30) than in the persistent AF/long-standing persistent AF cohort (male: 73.3% vs female: 67.3%; P = .40). These effectiveness rates compare favorably with early clinical experience with PFA . However, none of the previous studies examining PFA for AF reported clinical outcomes according to sex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15,23 The other clinical effectiveness data published with PFA were from the recently published inspIRE study (A Study for Treatment of Paroxysmal Atrial Fibrillation [PAF] by Pulsed Field Ablation [PFA] System with Irreversible Electroporation) using a different circular PFA catheter system: 186 patients with paroxysmal AF underwent PFA at 13 centers, and the 1-year Kaplan-Meier estimate of freedom from AF/AFL/AT was 70.9%. 24 Also reported recently, the 1-year clinical effectiveness in the PULSED AF study (Pulsed Field Ablation to Irreversibly Electroporate Tissue and Treat AF) using yet another circular PFA catheter system was 66.2% and 55.1% for paroxysmal and persistent AF, respectively. 23 In comparing these various studies, one should be cognizant that the observed higher freedom from atrial tachyarrhythmia recurrence in MANIFEST-PF may reflect differences in monitoring intensity.…”
Section: Discussionmentioning
confidence: 76%
“…14,15,23 The AF underwent PFA at 13 centers, and the 1-year Kaplan-Meier estimate of freedom from AF/AFL/AT was 70.9%. 24 Also reported recently, the 1-year clinical effectiveness in the PULSED AF study (Pulsed Field Ablation to Irreversibly Electroporate Tissue and Treat AF) using yet another circular PFA catheter system was 66.2% and 55.1% for paroxysmal and persistent AF, respectively. 23 In comparing these various studies, one should be cognizant that the observed higher freedom from atrial tachyarrhythmia recurrence in MANIFEST-PF may reflect differences in monitoring intensity.…”
Section: Clinical Effectivenessmentioning
confidence: 76%